A Literature Review: A Comprehensive Analysis of Type 2 Diabetes Mellitus in Productive-Age Adults and Adolescents in Indonesia - Elizabeth Haryanti (Journal of Literature Review, 2026)
Type 2 Diabetes Mellitus (T2DM), traditionally associated with older adults, has emerged as a critical public health crisis among younger populations globally, with Indonesia representing a significant and rapidly growing epicenter. This phenomenon, where diagnosed cases represent merely the "tip of the iceberg" with a vast, undiagnosed, and at-risk population submerged beneath, is particularly alarming in productive-age adults (20-59 years) and adolescents. This literature review synthesizes current evidence from 2015 to 2024 to explore the scale, determinants, clinical peculiarities, socioeconomic impacts, and management challenges of early-onset T2DM in Indonesia. The review reveals a potent interplay of genetic predisposition, driven by the thrifty genotype hypothesis, and profound environmental triggers, including Indonesia's rapid nutrition transition towards energy-dense diets and pervasive physical inactivity. The unique pathophysiology in the young, marked by more aggressive beta-cell decline and pronounced insulin resistance, leads to quicker complications, devastating personal and national economic productivity. Systemic challenges, including fragmented healthcare, low health literacy, and significant stigma, further hinder effective prevention and management. The review concludes that addressing this "iceberg" requires a paradigm shift towards transformative, multi-sectoral policies that prioritize primordial and primary prevention, integrate technology for screening and education, and foster youth-empowering, culturally-tailored interventions to avert a future tsunami of diabetes-related morbidity and economic strain.